Pengaruh Motivasi, Komunikasi dan Stres Kerja terhadap Kepuasan Kerja Karyawan pada PT. Rama Gemilang Energi Indopersada Batam - Saono, Muhammad Malik Maulana; Auzar, Silvia Revana (Universitas Batam, 2021)
The purpose of this study is to determine whether the variables of motivation, communication and work stress affect the variable job satisfaction where the approach taken in this study is a quantitative approach through correlational research or looking for the influence between independent variables and the dependent variable. The total number of objects of this research are all employees at PT. Rama Gemilang Energi Indopersada Batam opened 52 people while the sample used was a census sample. In this case the researcher's data collection is by distributing questionnaires directly to the respondents and then using the SPSS program where the results of the multiple linear regression test, validity test and reliability test will be obtained. to increase job satisfaction increase employee perceived motivation, effective communication within the organization and employee work stress must be managed in order to increase job satisfaction.